The Relevance of the Implementation of the Omnibus Law and Efforts to Save the Indonesian Environment - Tamaulina Br Sembiring; Irma Rachmawati Maruf; B.M.A.S. Anaconda Bangkara; Deden Sumantry; Yeti Rohayati (Budapest International Research and Critics University, 2022)
Finding the relevance of the implementation of communication and efforts to save the Indonesian environment is the main objective of this study through a study the summation of documents and literature related to issues that have recently been approved by parliament by examining some scientific pieces of evidence that have been published, especially in the last three years. We examine the findings of the loading technique data, in-depth evaluation, and concluding to get valid answers to questions. Our data search was conducted electronically on the legal science literature database, especially omnibus and its relation to protecting a healthy environment in Indonesia. Based on the evidence we got and the discussion, we can conclude that the implementation of the omega slow realization, which should lead to the protection of Indonesia's environmental sustainability, has experienced a setback compared to the previous law products, so substantially, the material of the Law still ignores environmental protection, especially with the lack of participation of society as expected. Thus, this finding becomes a vital force for the development of similar studies in the future.